Metabolic regulation of macrophage proliferation and function in atherosclerosis. Issue 5 (October 2021) - Patterson, Michael T.; Williams, Jesse W.
Abstract : Purpose of review: Macrophage accumulation within atherosclerotic plaque is a primary driver of disease progression. However, recent advances in both phenotypic and functional heterogeneity of these cells have allowed for improved insight into potential regulation of macrophage function within lesions. In this review, we will discuss recent insights on macrophage heterogeneity, lipid processing, metabolism, and proliferation in atherosclerosis. Furthermore, we will identify outstanding questions in the field that are pertinent to future studies. Recent findings: With the recent development of single-cell RNA sequencing, several studies have highlighted the diverse macrophage populations within plaques, including pro-inflammatory, anti-inflammatory, lipid loaded and tissue resident macrophages. Furthermore, new data has suggested that differential activation of metabolic pathways, including glycolysis and fatty acid oxidation, may play a key role in determining function. Recent works have highlighted that different populations retain varying capacity to undergo proliferation; regulating the proliferation pathway may be highly effective in reducing plaque in advanced lesions. Summary: Macrophage populations within atherosclerosis are highly heterogeneous; differences in cytokine production, lipid handling, metabolism, and proliferation are seen between subpopulations. Understanding the basic cellular mechanisms that drive this heterogeneity will allow for the development of highly specific disease modulating agents to combat atherosclerosis.